THE CONCEPT OF ISLAMIC BANKING AND FINANCE : A LITERATURE REVIEW - Eko Suyono (Sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2017)
ABSTRACTThe concept of Islamic banking and finance significantly departs from its basic sources which are Quran and Sunna of the Prophet. Both sources strictly prohibit riba (usury) and gharar (gambling) in financial transactions and recommend for profit and loss sharing basis. Based on this principles, many Islamic financial experts and scholars try to develop some financial products which are in-line with the Islamic principles. Since then, Islamic banking provides several financial products such as Mudharaba, Murabaha, Musharaka, Istisna’a, Ijarah, Salam, etc, which are not violating the Islamic principles. When Muslims are able to utilize the Islamic principles in financing the business, thus the Islamic banking will be the best alternative for Muslim populace around the world.